The Effect of Quality of Service on Customer Satisfaction in PT. PLN (PERSERO) Region Unit North Sumatra - Sophia Rahmadhani; Wahyu Syarvina (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2022)
The effect of quality of service on customer satisfaction at PT. PLN (Persero) Region Unit North Sumatra. The purpose of this study is (1) to determine the quality of service at PT. PLN (Persero) Region Unit North Sumatra. (2) Knowing the level of customer satisfaction PT. PLN (Persero) Region Unit North Sumatra. To achieve this, researchers used data collection techniques through interviews, documentation and observation. The data obtained from the research results were processed using qualitative descriptive analysis. PT. PLN (Persero) Region Unit North Sumatra provides services according to standard operating procedures, employees are also friendly and polite. Service satisfaction can be felt by customers because PT. PLN itself is quite responsive in terms of what customers ask for. Customer satisfaction is the main thing for PT. PLN (Persero) Region Unit North Sumatra The more satisfied customers are, the better the picture of PT. PLN in the eyes of customers.